Determination of C-13 CSA tensors: extension of the model-independent approach to an RNA kissing complex undergoing anisotropic rotational diffusion in solution - Ravindranathan, S; Kim, CH; Bodenhausen, G (Journal of Biomolecular NMR, 2005)
Chemical shift anisotropy (CSA) tensor parameters have been determined for the protonated carbons of the purine bases in an RNA kissing complex in solution by extending the model-independent approach [Fushman, D., Cowburn, D. (1998) J. Am. Chem. Soc. 120, 7109-7110]. A strategy for determining CSA tensor parameters of heteronuclei in isolated X-H two-spin systems (X = C-13 or N-15) in molecules undergoing anisotropic rotational diffusion is presented. The original method relies on the fact that the ratio kappa(2)=R-2(auto)/R-2(cross) of the transverse auto- and cross-correlated relaxation rates involving the X CSA and the X-H dipolar interaction is independent of parameters related to molecular motion, provided rotational diffusion is isotropic. However, if the overall motion is anisotropic kappa(2) depends on the anisotropy D parallel to/D-perpendicular to of rotational diffusion. In this paper, the field dependence of both kappa(2) and its longitudinal counterpart kappa(1)=R-1(auto)/R-1(cross) are determined. For anisotropic rotational diffusion, our calculations show that the average kappa(av) = 1/2 (kappa(1)+kappa(2)), of the ratios is largely independent of the anisotropy parameter D parallel to/D-perpendicular to. The field dependence of the average ratio kappa(av) may thus be utilized to determine CSA tensor parameters by a generalized model-independent approach in the case of molecules with an overall motion described by an axially symmetric rotational diffusion tensor.
Keywords: anisotropic rotational diffusion; chemical shift anisotropy tensors; cross-correlation; model-independent approach; NMR

Oxidation of norbornene over vanadium-substituted phosphomolybdic acid catalysts and spectroscopic investigations - Raj, N. K. K.; Ramaswamy, A.; Manikandan, Palanichamy (Journal of Molecular Catalysis A-Chemical, 2005)
Oxidation of norbornene has been carried out over mono-, di- and tri-vanadium-substituted phosphomolybdic acid catalysts with aqueous hydrogen peroxide (aq. H2O2) as an oxidant in different solvents. Monovanadium-substituted phosphomolybdic acid catalyst was found to be better than other catalysts for the above reaction and acetonitrile was the suitable solvent. At the optimum temperature of 60 degreesC, the norbornene conversion was 70% and the selectivity for 2,3-epoxy norbornane was 58%. The side products were norborneols and 2-norbornanone. The lower selectivity of 2,3-epoxy norbornane with aq. H2O2 is attributed to the simultaneous formation of other products, norborneols and 2-norbornanone. The norborneols are formed from norbornene by acid-catalyzed reaction. Other oxidants like urea-hydrogen peroxide adduct (UHP) and tert-butyl hydrogen peroxide (TBHP) were also tested for norbornene oxidation reaction. With UHP, the conversion was almost same (69%) as that of aq. H2O2 reaction; however, 2,3-epoxy norbornane was the main product with >97% selectivity. Thus, the overall yield was 66.9% at 60 degreesC after 4 h. The high selectivity with UHP is attributed to the controlled release of H2O2, absence of water and less acidic nature of UHP. With TBHP the selectivity for the epoxide was >96%; however, the conversion was low (27%). A mechanism for the norbornene oxidation is believed to be proceeding via V(5+)-peroxo and V(4+)-superoxo intermediates. NMR, EPR and UV-vis spectroscopic techniques were employed to understand the reaction intermediates and reaction pathways. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: 2; 3-epoxy norbornane; aq. H2O2; epoxidation; EPR; NMR; norbornene; urea-H2O2 adduct; UV-Vis; vanadium-substituted phosphomolybdic acid

Synthesis and characterization of poly(higher-alpha-olefin)s with a nickel(alpha-diimine)/methylaluminoxane catalyst system: effect of chain running on the polymer properties - Subramanyam, Ummadisetty; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2007)
Homopolymerization of octadecene-1 at different reaction conditions has been studied. Significant chain running can be seen at higher polymerization temperatures. Interestingly, insertion of octadecene-1 into a sterically hindered nickel-cation/carbon (secondary) bond is observed. The microstructure of the polymer was established using NMR spectroscopy. The effects of chain running on polymer melting, crystallization behavior, and dynamic mechanical thermal properties were studied using DSC and DMTA. The extent of chain running (i.e., 2 omega-, 1,omega-enchainments) decreases with an increase in the carbon number of alpha-olefins. (c) 2006 Wiley Periodicals, Inc.
Keywords: chain running; Crystallization; glass transition; melt transition; nickel (alpha-diimine); NMR; poly(alpha-olefin)s

Synthesis, characterization, and acoustic properties of new soluble polyurethanes based on 2,2 `-[1,4-phenylenebis(nitrilomethylylidene)diphenol and 2,2 `-[4,4 `-methylene-di-2-methylphenylene-1,1 `-bis(nitrilomethylylidene)]diphenol - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Eight novel polyurethanes based on 2,2'-[1,4-phenylenebis(nitrilomethylylidene)]diphenol and 2,2-[4,4'methylene-di-2-methylphenylene-1,1'-bis(nitrilomethylylidene) ]diphenol acting as hard segments with two aromatic and two aliphatic diisocyanates (4,4'-diphenytmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) were prepared and characterized with Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1-NMR and C-13-NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis. All the polyurethanes contained domains of semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties and solubility parameters were calculated with the group contribution method. (c) 2007 Wiley Periodicals, Inc.
Keywords: infrared spectroscopy; NMR; phase behavior; polyurethanes; Thermal properties

Structural elucidation of propargylated products of 3-substituted-1,2,4-triazole-5-thiols by NMR techniques - Chaudhary, Preeti M.; Chavan, Sayalee R.; Kavitha, M.; Maybhate, Shailaja P.; Deshpande, Sunita R.; Likhite, Anjali P.; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2008)
Propargylation of 3-substituted-1,2,4-triazole-5-thiols, which predominantly exist as their thione tautomers, was carried out with the view to synthesize different heterocycles and study their biological activity. Three different products namely, a mono S-propargyl and two S,N-dipropargyl regioisomers, arising from N1/N2 substitution, were isolated and characterized. Unambiguous structural elucidation of the regioisomers of S,N-dipropargyl derivatives was achieved by means of (13)C-(1)H HMBC technique. The proportion of the regioisomers was found to vary with the substituent on the 1,2,4-triazole thiols. No product corresponding to N4 substitution was isolated from any of the reactions carried out. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: (1)H NMR; (13)C NMR; (15)N NMR; 1; 2; 4-triazoles; HMBC; NMR; Regioisomers

Increase in backbone mobility of the VTS1p-SAM domain on binding to SRE-RNA - Ravindranathan, Sapna; Oberstrass, Florian C.; Allain, Frederic H. T. (Journal of Molecular Biology, 2010)
The sterile alpha motif (SAM) domain of VTS1p, a posttranscriptional gene regulator, belongs to a family of SAM domains conserved from yeast to humans. Even though SAM domains were originally classified as protein-protein interaction domains, recently, it was shown that the yeast VTS1p-SAM and the SAM domain of its Drosophila homolog Smaug can specifically recognize RNA hairpins termed Smaug recognition element (SRE). Structural studies of the SRE-RNA complex of VTS1p-SAM revealed that the SAM domain primarily recognizes the shape of the RNA fold induced by the Watson-Crick base-pairing in the RNA pentaloop. Only the central G nucleotide is specifically recognized. The VTS1p-SAM domain recognizes SRE-RNAs with a CNGGN pentaloop where N is any nucleotide. The C1-G4 base pair in the wild type can be replaced by any pair of nucleotides that can form base pairs even though the binding affinity is greatest with a pyrimidine in position 1 and a purine in position 4. The interaction thus combines elements of sequence-specific and non-sequence-specific recognitions. The lack of structural rearrangements in either partner following binding is rather intriguing, suggesting that molecular dynamics may play an important role in imparting relaxed specificity with respect to the exact combination of nucleotides in the loop, except for the central nucleotide. In this work, we extend our previous studies of SRE-RNA interaction with VTS1p, by comparing the dynamics of the VTS1p-SAM domain both in its free form and when bound to SRE-RNA. The 1 5 N relaxation studies of backbone dynamics suggest the presence of a dynamic interaction interface, with residues associated with specific G3 recognition becoming more rigid on RNA binding while other regions attain increased flexibility. The results parallel the observations from our studies of dynamics changes in SRE-RNA upon binding to VTS1p-SAM and shows that molecular dynamics could play a crucial role in modulating binding affinity and possibly contribute to the free energy of the interaction through an entropy-driven mechanism. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: (15)N relaxation; NMR; protein-RNA interaction; SRE-RNA; VTS1p-SAM domain

Synthesis and stereochemistry of highly crowded N-benzylpiperidones - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2012)
A series of N-benzylated 3,5-diakyl-2,6-diarylpiperidin-4-ones 4-8 were conveniently synthesized in significant yields of 68-88% by N-benzylation of the corresponding 2,6-diaryl-3,5-dimethylpiperidin-4-ones 1-3 using different benzyl bromides. Initially, the new piperidone 2,6-bis(4-ethoxypheny1)-3,5-dimethylpiperidin-4-one 3 was synthesized by the condensation of 1:1:2 M ratio of 3-pentanone, ammonium acetate and para-ethoxybenzaldehyde in ethanolic medium. All the synthesized new compounds 3-8 were characterized by their analytical and spectral (IR, H-1 and C-13 NMR) interpretations. The stereochemistry of the new piperidone 3 was elucidated as chair conformation with an equatorial orientation of all substituents, suggested by its vicinal couplings from H-1 NMR spectrum. To investigate the impact on piperidone stereochemistry as well as NMR chemical shifts, all the N-benzylated products 4-8 were compared with their corresponding precursors, and as a result, it is clearly established that all the synthesized N-benzyl piperidones exist in the chair conformation with an equatorial orientation of all the substituents at C-2, C-3, C-5, C-6 and N. Contrary to the probability all N-benzylated compounds retain the same conformation and configuration as their precursors, however, a remarkable change on the chemical shifts are observed. For the further unambiguous confirmation of stereochemistry, the 1-benzyl-3,5-dimethyl-2,6-diphenylpiperidin-4-one 4 was examined by single-crystal X-ray diffraction. The compound 4, C26H27NO, crystallized in a P-1 space group under triclinic system with unit cell dimensions a, b, c (angstrom) and alpha, beta, gamma (degrees) of 10.156(2), 11.002(2), 11.348(4) and 116.74(4), 100.81(3), 100.17(3), respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chair conformation; Configuration; crystal structure; N-benzylation; NMR; Piperidin-4-one

Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

GIAO/DFT studies on 1,2,4-triazole-5-thiones and their propargyl derivatives - Phalgune, Usha D.; Vanka, Kumar; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2013)
Density functional theory (DFT)/Becke-Lee-Yang-Parr (B3LYP) and gauge-including atomic orbital (GIAO) calculations were performed on a number of 1,2,4-triazole derivatives, and the optimized structural parameters were employed to ascertain the nature of their predominant tautomers. C-13 and N-15 NMR chemical shifts of 3-substituted 1,2,4-triazole-5-thiones and their propargylated derivatives were calculated via GIAO/DFT approach at the B3LYP level of theory with geometry optimization using a 6-311++G** basis set. A good agreement between theoretical and experimental C-13 and N-15 NMR chemical shifts could be found for the systems investigated. The data generated were useful in predicting N-15 chemical shifts of all the nitrogen atoms of the triazole ring, some of which could not be obtained in solution state N-15 HMBC/HSQC NMR measurements. The energy profile computed for the dipropargylated derivatives was found to follow the product distribution profile of regioisomers formed during propargylation of 1,2,4-triazole thiones. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: 1; 2; 4-triazole-5-thiones; C-13; DFT; GIAO; N-15; NMR; Regioisomers; tautomers

Structural investigations of porous MgCl2-2-butanol molecular adduct as support for olefin polymerization - Thushara, K. S.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2014)
A new heterogeneous Ziegler-Natta (Z-N) catalyst support material, MgCl2 center dot 4(CH3CH(OH)CH2CH3) (Mg2BuOH) has been synthesized. 2-Butanol, a linear, secondary alcohol was chosen for the generation of an active MgCl2 support which results in a Z-N catalyst with TiCl4. Significant feature of this work is the formation of rod shaped molecular adduct with highly porous character. Adduct material is characterized by XRD, TG-DTA, Raman spectroscopy, solid-state NMR and SEM. Activity of the Z-N catalyst supported on Mg2BuOH for ethylene polymerization is comparable with that of commercially available heterogeneous Z-N catalyst. However, there is scope to improve the activity by optimizing textural properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; NMR; Polyolefin; Ziegler-Natta catalyst

Supramolecular transitions in native cellulose-I during progressive oxidation reaction leading to quasi-spherical nanoparticles of 6-carboxycellulose - Sharma, Priyanka R.; Rajamohanan, Pattuparambil R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Cellulose-I swells considerably in phosphoric acid, and converts to amorphous cellulose via a cellulose-II transition state. Controlled oxidation of cellulose-I to 6-carboxycellulose (6CC) using HNO3-H3PO4-NaNO2 oxidation system led to the selective production of 6CC's of varying carboxyl contents (1.7-22%) as well as various shapes and sizes (macro-sized fibrils of several micron length and/or spherical nanoparticles of 25-35 nm), depending on the reaction conditions. 6CC's having less than 14% carboxyl content were largely in cellulose-II form (WAXRD values in-between cellulose I and cellulose II), whereas at 14-22% the 6CC's were largely amorphous; only trace crystallinity was observed at 19% and 22% carboxyl 6CC. Spherical nanoparticles retained a high degree of crystallinity having cellulose-I structure, whereas the macro-sized fibrils were largely converted to cellulose-II structure. Analysis by WAXRD as well as by CP-MAS C-13 NMR studies gave similar conclusions. Reduced molecular weight with progressive oxidation, including presence of oligomers, was also evident from an increase in the reducing-end carbon peak at similar to 92 ppm. For high oxidation levels (>14%) the NMR 92-96 ppm peaks disappeared on extracting with dilute alkali, due to soluble oligomers being removed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxycellulose; cellulose; Nanoparticles; NMR; WAXRD

Prediction of bioactive compounds using computed NMR chemical shifts - Karthikeyan, Muthukumarasamy; Rajamohanan, Pattuparambil Ramanpillai; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
NMR based chemical shifts are an important diagnostic parameter for structure elucidation as they capture rich information related to conformational, electronic and stereochemical arrangement of functional groups in a molecule which is responsible for its activity towards any biological target. The present work discusses the importance of computing NMR chemical shifts from molecular structures. The NMR chemical shift data (experimental or computed) was used to generate fingerprints in binary formats for mapping molecular fragments (as descriptors) and correlating with the bioactivity classes. For this study, chemical shift data derived binary fingerprints were computed for 149 classes and 4800 bioactive molecules. The sensitivity and selectivity of fingerprints in discriminating molecules belonging to different therapeutic categories was assessed using a LibSVM based classifier. An accuracy of 82% for proton and 94% for carbon NMR fingerprints were obtained for anti-psoriatic and anti-psychotic molecules demonstrating the effectiveness of this approach for virtual screening.
Keywords: Chemical shift; fingerprints; NMR; similarity searching; virtual screening

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

N-terminal domain of polypyrimidine-tract binding protein is a dynamic folding platform for adaptive RNA recognition - Damberger, Fred F.; Krepl, Miroslav; Arora, Rajika; Beusch, Irene; Maris, Christophe; Dorn, Georg; Sponer, Jiri; Ravindranathan, Sapna; Allain, Frederic H-T (NUCLEIC ACIDS RESEARCH, 2024)
Keywords: CHEMICAL-SHIFT ANISOTROPY; NMR; ROTATING-FRAME RELAXATION; TIME-SCALE DYNAMICS

Recommendations for sample selection, collection and preparation for NMR-based metabolomics studies of blood - Emwas, Abdul-Hamid; Zacharias, Helena U.; Alborghetti, Marcos Rodrigo; Gowda, G. A. Nagana; Raftery, Daniel; Mckay, Ryan T.; Chang, Chung-ke; Saccenti, Edoardo; Gronwald, Wolfram; Schuchardt, Sven; Leiminger, Roland; Merzaban, Jasmeen; et al. (Metabolomics, 2025)
BackgroundMetabolic profiling of blood metabolites, particularly in plasma and serum, is vital for studying human diseases, human conditions, drug interventions and toxicology. The clinical significance of blood arises from its close ties to all human cells and facile accessibility. However, patient-specific variables such as age, sex, diet, lifestyle and health status, along with pre-analytical conditions (sample handling, storage, etc.), can significantly affect metabolomic measurements in whole blood, plasma, or serum studies. These factors, referred to as confounders, must be mitigated to reveal genuine metabolic changes due to illness or intervention onset.Review objectiveThis review aims to aid metabolomics researchers in collecting reliable, standardized datasets for NMR-based blood (whole/serum/plasma) metabolomics. The goal is to reduce the impact of confounding factors and enhance inter-laboratory comparability, enabling more meaningful outcomes in metabolomics studies.Key conceptsThis review outlines the main factors affecting blood metabolite levels and offers practical suggestions for what to measure and expect, how to mitigate confounding factors, how to properly prepare, handle and store blood, plasma and serum biosamples and how to report data in targeted NMR-based metabolomics studies of blood, plasma and serum.
Keywords: Blood; Metabolites; Metabolomics; NMR; Plasma; Serum; Standardization